EFFECTS OF FEEDING RATE REDUCTION ON THE GROWTH PERFORMANCE AND FEED UTILIZATION OF PACIFIC WHITE SHRIMP REARED USING BIOFLOC SYSTEM - Kusmiatun, Anik; Utami, Diah Ayu Satyari; Firnaeni, Tata; Kaborang, Yasinta Ega; Harijono, Teguh; Tangguda, Sartika; Triyastuti, Meilya Suzan; Djauhari, Ricky; Tantulo, Uras; Sihombing, Mika Azarya (Jurnal Riset Akuakultur, 2024)
Biofloc in shrimp aquaculture provides natural food and reduces the reliance on commercial feed. The extent to which biofloc can optimize feeding management is not, however, fully understood. This study aimed to evaluate the effects of reducing feeding rates on the growth performance and feed utilization of Pacific white shrimp (Litopenaeus vannamei) reared in a biofloc system. A completely randomized design was used with four treatments: K (standard feeding, clear water), N (standard feeding, biofloc), NA (25% feeding reduction, biofloc), and NB (50% feeding reduction, biofloc). Shrimp were stocked at 40 individuals per tank and fed commercial feed containing 40% protein over a 30-day period. Results showed that shrimp in the NA treatment (25% feed reduction with biofloc) had the highest final weight (8.66 ± 0.03 g), biomass (306.13 ± 14.27 g), and weight gain (5.74 ± 0.25 g) compared to other treatments (P<0.05). NA also exhibited a higher specific growth rate (3.63 ± 0.27 %/day) than K and NB. Feed utilization improved with a lower feed conversion ratio and higher protein retention in the NA group. This study highlights that a 25% feeding rate reduction in biofloc systems optimizes shrimp growth and feed utilization. Future research should explore long-term sustainability, biofloc composition variations, and technological integration for scaling up efficient and environmentally sustainable shrimp farming operations.Penggunaan bioflok dalam budidaya udang memberikan makanan alami dan mengurangi ketergantungan pada pakan komersial. Namun, sejauh mana bioflok dapat mengoptimalkan manajemen pakan belum sepenuhnya dipahami. Penelitian ini bertujuan untuk mengevaluasi efek pengurangan laju pemberian pakan terhadap kinerja pertumbuhan dan pemanfaatan pakan udang vaname (Litopenaeus vannamei) yang dibudidayakan dalam sistem bioflok. Desain penelitian menggunakan rancangan acak lengkap (RAL) dengan empat perlakuan, yaitu: K (pemberian pakan standar, air jernih), N (pemberian pakan standar, bioflok), NA (pengurangan pakan 25%, bioflok), dan NB (pengurangan pakan 50%, bioflok). Udang ditempatkan sebanyak 40 individu per tangki dan diberi pakan komersial yang mengandung 40% protein selama 30 hari. Hasil menunjukkan bahwa udang pada perlakuan NA (pengurangan pakan 25% dengan bioflok) memiliki berat akhir tertinggi (8,66 ± 0,03 g), biomassa (306,13 ± 14,27 g), dan kenaikan berat (5,74 ± 0,25 g) dibandingkan perlakuan lainnya (P<0,05). NA juga menunjukkan tingkat pertumbuhan spesifik yang lebih tinggi (3,63 ± 0,27 %/hari) dibandingkan K dan NB. Pemanfaatan pakan meningkat dengan rasio konversi pakan yang lebih rendah dan retensi protein yang lebih tinggi pada kelompok NA. Penelitian ini menunjukkan bahwa pengurangan feeding rate pakan sebesar 25% dalam sistem bioflok mengoptimalkan pertumbuhan udang dan pemanfaatan pakan. Penelitian di masa depan harus mengeksplorasi keberlanjutan jangka panjang, variasi komposisi bioflok, dan integrasi teknologi untuk meningkatkan praktik budidaya udang yang efisien dan ramah lingkungan.